2017
DOI: 10.1155/2017/7618419
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Mind‐Body Interaction from the Perspective of East Asian Medicine

Abstract: Objective Attempts to understand the emotion have evolved from the perspective of an independent cognitive system of the mind to that of an interactive response involving the body. This study aimed to quantify and visualize relationships between different emotions and bodily organ systems from the perspective of East Asian medicine. Methods Term frequency-inverse document frequency (tf-idf) method was used to quantify the significance of Five Viscera and the gallbladder relative to seven different emotions thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…An example of the second disease type is liver excess (U65), corresponding to menopausal climacteric symptoms and panic disorder. A previous study described the role of the liver in emotional states by reference to the classical medical text, DongUiBoGam [18]. Interestingly, panic disorder and menopausal climacteric symptoms identified by the doctors in this study were most frequently linked to liver excess, which accords with the link between emotional disorders and the visceral system assumed in Korean medicine.…”
Section: Discussionsupporting
confidence: 73%
“…An example of the second disease type is liver excess (U65), corresponding to menopausal climacteric symptoms and panic disorder. A previous study described the role of the liver in emotional states by reference to the classical medical text, DongUiBoGam [18]. Interestingly, panic disorder and menopausal climacteric symptoms identified by the doctors in this study were most frequently linked to liver excess, which accords with the link between emotional disorders and the visceral system assumed in Korean medicine.…”
Section: Discussionsupporting
confidence: 73%
“…In Cluster B (psychiatric symptoms), CV17 and HT7 were the specific acupoints. Traditional East Asian Medicine theories suggest that HT7 are effective in psychiatric symptoms due to the heart meridian's nature to regulate emotions [30]. Previous studies have shown that CV17 is used to treat Hwa-byung and anxiety [31,32], while HT7 is used to treat sleep disorders [33][34][35] and depression-related behaviours [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Another connection between emotions and respiratory health is acknowledged in East Asian medicine, noting the association between the lungs and feelings of sadness, grief, and anxiety [153] (. Table 51.3).…”
Section: Biological Stressmentioning
confidence: 99%